Tomography-based monitoring of isothermal snow metamorphism under advective conditions - P. P. Ebner; M. Schneebeli; A. Steinfeld (The Cryosphere, 2015)
Time-lapse X-ray microtomography was used to investigate the structural dynamics of isothermal snow metamorphism exposed to an advective airflow. The effect of diffusion and advection across the snow pores on the snow microstructure were analysed in controlled laboratory experiments and possible effects on natural snowpacks discussed. The 3-D digital geometry obtained by tomographic scans was used in direct pore-level numerical simulations to determine the effective permeability. The results showed that isothermal advection with saturated air have no influence on the coarsening rate that is typical for isothermal snow metamorphism. Isothermal snow metamorphism is driven by sublimation deposition caused by the Kelvin effect and is the limiting factor independently of the transport regime in the pores.